W2 In situ simulation: plan hard, fight easy. (November 2018) - Wright, David; Purva, Makani; Blackmore, Andrew; Caines, Kim
Abstract : Introductory and intermediate Background: In situ simulation is increasingly recognised as offering many potential advantages. These include the benefits of team training, ease and equality of access, integration into routine working practices and identification of latent errors. 1 However, establishing and sustaining an in situ programme poses particular challenges. We aim to provide a framework for the process from planning in situ scenarios and common pitfalls to effective strategies for establishing a programme in your organisation. Intended learning outcomes: Understand the rationale and scope of in situ simulation Recognise the planning and logistical requirements of in situ simulation Plan a mock in situ simulation from start to finish Explore the role of situ simulation in improving quality and safety. Structure: Delegates will spend the majority of this workshop in facilitated groups planning in situ simulations, using real clinical settings. Delegates will be provided with a range of materials and techniques to enable the recreation these environments and facilitate specific plans. There will be a focus on: Practical and technical considerations Maintaining a normal service Process testing Safety and latent errors Timetable: 00–15 Safety, service and errors 15–45 Groups: planning 45–60 Groups: feedback and discussion Educational methods: The workshop focuses on a number of case studies including; the underperforming trauma team, escalation strategies on a midwifery-led birth unit and operating theatre team effectiveness. This includes: Facilitated group tasks Immersive 360° stills and video: allow delegates to explore the clinical setting Materials to support planning, technical needs and practical aspects Presentation and discussion of completed in situ plans Generating a follow up report with risk stratification. Reference: Fent G, Blythe J, Farooq O, et al . In situ simulation as a tool for patient safety: A systematic review identifying how it is used and its effectiveness. BMJ Simulation and Technology Enhanced Learning 2015;1:103–110.